Sexual and reproductive health "Train The Trainer" programs in low- and middle-income countries: a scoping review - Felicity R A Hughes; Jessica R Botfield; Kevin McGeechan (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Universal access to reproductive health care including family planning and sexual health care are recognised as human rights and are a key contributor to the United Nations' (UN) Sustainable Development Goals, yet many people across the globe have limited access to information and services to protect their sexual and reproductive health (SRH). Universal access cannot be achieved without a skilled health workforce. 'Train the Trainer' (TTT) approaches are commonly advocated as cost-effective and sustainable options for building health capacity through up-skilling health workforces. # Methods A scoping review was undertaken to identify the type and extent of the available literature on sexual and reproductive health TTT programs in low- and middle-income (LMI) countries, in order to gain insights to inform practice and fill the knowledge gaps to inform future research. Six databases were used as the source of information (CINAHL, EMBASE, ERIC, Global Health, Medline and Scopus). # Results A systematic search returned a total of 700 studies. After duplicate removal, 487 studies were screened by year, title and abstract, and 39 studies were identified for full text review. After the full text review, 16 studies were deemed to meet the criteria for final inclusion. Findings show that much of the published literature on SRH TTT programs reports on HIV training in African countries. Thematic analysis revealed a wealth of practical considerations for practitioners wishing to implement SRH TTT programs in LMI country settings. # Conclusions This scoping review identified a paucity of recent peer-reviewed literature available on SRH TTT programs in LMI country settings. Despite this, a number of practical considerations remain, relating to TTT methodology and design; factors that support or inhibit implementation; and sustainability and scaling up were identified. Future research should focus on adopting stronger outcome evaluation methodology to determine effectiveness of TTT programs; and investigate the application of TTT models across a range of SRH topics in a diverse range of LMI countries.